FBN1 Mutation Screening in a Marfan Syndrome Patient - Amallia Setyawati; Nani Maharani; Sultana Faradz; Gerard Pals; Sodiqur Rifqi; Muhammad Sungkar (RSUP Dr. Kariadi, 2015)
Background : MFS is characterized by variable clinical manifestations mainly in cardiovascular, ocular, and skeletal systems. The major encoding gene of structural constituent of extracellular microfibrils is Fibrillin-1 (FBN1). Approximately 90% of MFS cases are caused by mutations in the FBN1 gene (15q21.1) and the other second is TGFBR2 (3p22) gene. Methods : The UMD database, Ensemble database and VUmc DNA Laboratory database of FBN1 mutations and polymorphisms were used to evaluate the DNA variations. For paternity testing, the PowerPlex system (Promega Corp. USA) was used. A 30-years old was being admitted to the hospital. CKMB and Troponin C serial. A CT angiography was performed and revealed a long type 1 aortic dissection until proximal of bifurcation, the arm span-height ratio is 1.10, high myopia, arachnodactily, positive thumb signs and wrist signs, joint laxity articulation genu, and history of spontaneous pneumothorax. Identified, his mother, two sisters and one brother are clinically MFS. Results : Genetic testing of FBN1 showed a substation at exon 15 of FBN1, c.1924G>T. Discussion: In missense mutations substituting or creating cysteine, the probability of ectopia lentis is significantly higher compared to other missense mutations. The EGF domains are interrupted by seven transforming growth factor (TGF)-binding protein domains characterized by 8 cysteine residues involved in intra-domain disulfide bonds. Conclusion : Untreated, life expectancy of patients with MFS is considerably reduced. Clinical care is complicated by variable age at onset and the wide range of severity of aortic features. Early recognition of affected status hopefully will lead to early prevention of complications that may follow.